Whose right to the city? An analysis of the mediatized politics of place surrounding alojamento local issues in Lisbon and Porto - Torkington, Kate (2021)
In view of the proliferation of alojamento local (short-term vacation rentals) in the major Portuguese cities of Lisbon and Porto, along with the recent transformation of the historic city centre neighbourhoods, this study explores the mediatized politics of place by analysing data sets resulting from different, but interconnected, discursive practices. At the level of governance, we examine how legislation has enabled and facilitated this transformation. We then explore the media coverage of the issues surrounding these recent changes. Finally, we focus on individual and collective stakeholder voices by analysing the various rights claims and arguments found in social media communication channels. Framing our analysis initially in Lefebvre's concept of 'the right to the city', often invoked as an argument for the promotion of justice, inclusion and sustainability in the face of urbanisation policies, we argue that a 'rights in the city' approach is better suited to gaining insight into the multiple tensions and conflicts brought about through the interlinking processes of regeneration, gentrification and touristification that affect neighbourhoods with high proportions of short-term rental accommodation, and conclude that there are many rights claimants within a seemingly unified group of stakeholders, invoking rights claims which are sometimes overlapping, but often conflicting.